ASUPAN PROTEIN DAN CAIRAN DENGAN KEJADIAN EDEMA PERIFER PASIEN DENGAN HEMODIALISIS RUTIN - Nirmalasari Nirmalasari; Yade K. Yasin; Hasmyati Hasmyati (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2026)
Chronic kidney disease (CKD) is a disorder of kidney function that can cause fluids, electrolytes, waste and metabolic toxins to accumulate in the body, requiring the patient to undergo hemodialysis therapy as a substitute for kidney function. In addition, CKD patients must monitor their diet, including protein and fluid intake, to prevent edema. The study aimed to determine the relationship between protein and fluid intake and incidence of peripheral edema in patients undergoing routine hemodialysis at Akademis Jaury Jusuf Putera Makassar Hospital. The research design used was analytical observational with a cross-sectional approach, involving 38 subject that met the inclusion criteria. Data on intake were collected using a 24-hour recall method, while data on peripheral edema were obtained through clinical examination. The correlational test was used the Spearman Rank test to determine the relationship between variables. In the study, the result of the univariate analysis showed that protein and fluid intake in patients undergoing routine hemodialysis were mostly in the aduquate categories, with some patients in the excessive category. Meanwhile, fluid intake was mostly in the excessive category, although some patients were still in the low and adequate categories. The correlational analysis showed a moderate relationship between protein intake and the occurrence of peripheral edema with a negative correlation direction (r=-0,355; p=0,029), and a strong relationship between fluid intake and the occurrence of peripheral edema with a positive correlation direction (r=0,692; p<0,001). Low protein intake was associated with the occurrence of peripheral edema, and excessive fluid intake was associated with the occurrence of peripheral edema.Penyakit ginjal kronik (PGK) adalah gangguan fungsi ginjal yang dapat menyebabkan cairan, elektrolit, limbah dan racun sisa metabolisme menumpuk dalam tubuh sehingga pasien memerlukan terapi hemodialisis sebagai pengganti ginjal. Selain itu, pasien PGK harus memperhatikan pengaturan diet termasuk pada asupan protein dan cairan untuk mencegah terjadinya edema. Penelitian ini bertujuan untuk mengetahui hubungan antara asupan protein dan cairan dengan kejadian edema perifer pasien dengan hemodialisis rutin di RS Akademis Jaury Jusuf Putera Makassar. Desain penelitian yang digunakan adalah observasional analitik dengan pendekatan cross sectional dan melibatkan 38 subjek yang memenuhi kriteria inklusi. Pengumpulan data asupan dilakukan dengan metode recall 24 jam, sedangkan data edema perifer dilakukan dengan pemeriksaan klinis. Uji hubungan yang digunakan adalah uji Spearman Rank untuk mengetahui hubungan antar variabel. Pada penelitian ini didapatkan hasil analisis univariat pada asupan protein dan cairan pasien yang menjalani hemodialisis rutin mayoritas dalam kategori adekuat dan rendah dan terdapat beberapa pasien dalam kategori berlebih, sedangkan pada asupan cairan mayoritas dalam kategori berlebih, namun masih terdapat beberapa pasien dalam kategori rendah dan adekuat. Hasil analisis korelatif terdapat hubungan yang cukup antara asupan protein dengan kejadian edema perifer dengan arah korelasi negatif (r=-0,355; p=0,029), dan terdapat hubungan yang kuat antara asupan cairan dengan kejadian edema perifer dengan arah korelasi positif (r=0,692; p<0,001). Asupan protein yang rendah berhubungan dengan kejadian edema perifer, dan asupan cairan yang berlebih berhubungan dengan kejadian edema perifer.